Preparation method and application of photosensitive activated Zn0. 8Cd0. 2S / PDI composite photocatalyst

The Zn0.8Cd0.2S/PDI composite photocatalyst was prepared by chemical synthesis method, and the PDI free radicals were activated by light irradiation, which solved the problem of difficult to effectively degrade polybrominated diphenyl ethers in the prior art, achieved efficient degradation of water pollutants and avoided environmental pollution. and harsh conditions improve the performance and application value of the catalyst.

CN119140153AActive Publication Date: 2024-12-17JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411293833.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

In the prior art, when dealing with difficult-to-degrade toxic organic matter, high-temperature incineration leads to environmental pollution, poor mechanical strength and stability of adsorption technology, high biodegradation cost and low efficiency, low photocatalyst dehalogenation efficiency and requires harsh conditions, and it is impossible to effectively degrade polybrominated bibenzene in water bodies. ether.

Method used

The Zn0.8Cd0.2S/PDI composite photocatalyst was prepared by chemical synthesis method, and PDI free radicals were activated by light irradiation, and near-infrared absorption was enhanced by solar spectrum to achieve efficient dehalogenation of aromatic halides, avoiding the time-consuming and time-consuming of traditional self-assembly processes. Harsh conditions.

Benefits of technology

The polybrominated diphenyl ether and 12 typical aromatic halides in the water were completely degraded within 2 minutes, improving the performance and practical application value of the catalyst, and it is stable in the air, without the need for unfriendly strong reducing agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140153A_ABST
    Figure CN119140153A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental material preparation, and discloses a preparation method and application of a photosensitive activated Zn0. 8Cd0. 2S / PDI composite photocatalyst. The method comprises the following steps: firstly, preparing PDI; the preparation method comprises the following steps: adding CTAB (Cetyltrimethyl Ammonium Bromide) into deionized water, stirring until the CTAB is dissolved, sequentially adding hexamethylenetetramine, citric acid monohydrate, cadmium nitrate tetrahydrate, zinc nitrate hexahydrate, PDI and thioacetamide, condensing and refluxing, stirring and reacting for a period of time, cooling to room temperature, repeatedly washing the reacted product with a NaCl solution and deionized water, and carrying out vacuum drying to obtain the Zn0. 8Cd0. 2S / PDI composite photocatalyst. According to the invention, resource waste and additional pollution cannot be caused, the operation is simple and convenient, and the composite material is green and environment-friendly; in addition, the purposes of thoroughly degrading decabromodiphenyl ether in a water body within 2 minutes by focusing natural sunlight and controllably treating aromatic halides in sewage are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental material preparation, and specifically relates to a photosensitive activated Zn 0.8 Cd 0.2 Preparation method and application of S / PDI composite photocatalyst. Background Art

[0002] With the application of a large number of building materials and the continuous industrial production of daily necessities, the excessive use of the flame retardant decabromodiphenyl ether is becoming more and more serious, and the biological toxicity caused by its low-bromine products "escaping" into the environment is becoming increasingly prominent. Pollutants remaining in water and soil accumulate in the human body through the transfer of the food chain, thus posing a potential threat to human health. Therefore, it is urgent to find a green and efficient method for degrading decabromodiphenyl ether.

[0003] At present, the main technologies for degrading decabromodiphenyl ether include high-temperature incineration, adsorption, biodegradation, chemical degradation, and photocatalytic technology. Since aromatic halogenide flame retardants are resistant to high temperatures and produce highly toxic low-bromine products after incineration, the traditional conventional high-temperature incineration technology will cause huge pollution to the environment when treating such difficult-to-degrade toxic organic matter; adsorption technology has the advantages of easy operation, low cost, high efficiency, and no highly toxic by-products, but its mechanical strength stability is poor and it is difficult to recycle and reuse; biodegradation is environmentally friendly, but it is expensive and has low degradation efficiency, making it difficult to be widely used; photocatalytic technology is not only simple in method and low in investment and operating costs, but also has strong reduction ability and high degradation rate, making it suitable for wide application. In addition, designing a high-performance catalyst is crucial in photocatalytic technology.

[0004] Perylene diimide (PDI) is a photosensitive organic semiconductor catalyst, which provides a promising solution due to its unique planar polycyclic aromatic structure and wide visible light absorption. They enhance the adsorption of polybrominated diphenyl ethers through π-π interactions and expand the light absorption range. However, due to the lack of polarized reduction sites and the inertness of XH covalent bonds, the original PDI as a catalyst faces challenges in the direct dehalogenation of aromatic halides. Therefore, it is necessary to select a suitable semiconductor to be combined with PDI for photocatalytic degradation reactions. The dehalogenation efficiency of PDI can be greatly improved by reducing it to PDI radicals, but common reducing agents such as triethylamine will still cause pollution to the environment, and PDI radicals are unstable and easily oxidized.

[0005] A self-assembled PDI diradical (PDI 2-) nanobelt catalysts are prepared by self-assembly under nitrogen conditions, but they are still unstable in oxygen-containing environments and the self-assembly process is time-consuming. Therefore, this study invented a photocatalytic material that can be stably stored in air and can be quickly activated by light. This study selected PDI as a polymer material, which can be used to construct a light-sensitive smart composite photocatalytic material. In addition, Zn 0.8 Cd 0.2 The addition of S can promote PDI to: PDI 2- In situ conversion of Zn 0.8 Cd 0.2 S / :PDI 2- The catalyst can make full use of the solar spectrum, enhance near-infrared absorption, and provide additional free radical reaction sites. It can achieve complete dehalogenation of 12 typical aromatic halides, including polybrominated diphenyl ethers, in trace amounts in water within 2 minutes, further optimizing the performance of the catalyst and having good practical application value. Summary of the invention

[0006] The purpose of the present invention is to solve the technical defects of low photocatalyst dehalogenation efficiency, slow electron transfer rate and high electron-hole recombination rate, and to prepare Zn by chemical synthesis. 0.8 Cd 0.2 S / PDI composite photocatalyst is applied to degrade aromatic halides in water.

[0007] In order to achieve the above technical purpose, the technical solution adopted by the present invention includes the following steps:

[0008] (1) Preparation of PDI:

[0009] 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), imidazole and β-alanine are mixed and calcined in a tube furnace at a constant temperature for a period of time under nitrogen protection. The resulting red solid is dispersed in ethanol, added with HCl solution and stirred overnight, washed with deionized water by centrifugation, and finally dried in a vacuum drying oven overnight to obtain the desired PDI.

[0010] (2) Photosensitive activated Zn 0.8 Cd 0.2 Preparation of S / PDI composite photocatalyst:

[0011] CTAB is added to deionized water and stirred until dissolved. Hexamethylenetetramine, citric acid monohydrate, cadmium nitrate tetrahydrate, zinc nitrate hexahydrate and PDI prepared in step (1) are added in sequence and heated. Finally, thioacetamide is added. After condensing and refluxing and stirring for a period of time, the mixture is cooled to room temperature. The obtained product is centrifuged, washed repeatedly with NaCl solution and deionized water, and finally dried in vacuum to obtain the final product, photosensitive activated Zn 0.8 Cd0.2 S / PDI composite photocatalyst.

[0012] Preferably, in step (1), the molar ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), imidazole and β-alanine is 1:50:5; and the concentration of the HCl solution is 2 mol / L.

[0013] Preferably, in step (1), the calcination temperature is 100-120° C., and the calcination time is 4-5 hours.

[0014] Preferably, in step (1), the vacuum drying temperature is 60-70° C. and the time is 10-12 h.

[0015] Preferably, in step (2), the usage ratio of CTAB, hexamethylenetetramine, citric acid monohydrate, cadmium nitrate tetrahydrate, zinc nitrate hexahydrate, PDI and thioacetamide is 0.86g::0.327g:0.243g:0.283g:1.093g:0.025~3.75g:0.345g.

[0016] Preferably, in step (2), the heating temperature is 80-85° C. and the heating time is 5-6 hours.

[0017] Preferably, in step (2), the concentration of the NaCl solution is 0.3%.

[0018] Preferably, in step (2), the vacuum drying temperature is 60-70° C. and the time is 10-12 h.

[0019] The Zn obtained by the above-mentioned preparation method 0.8 Cd 0.2 S / PDI composite photocatalyst, in which PDI accounts for Zn 0.8 Cd 0.2 The molar percentage of S is 1% to 15%.

[0020] The photosensitive activated Zn 0.8 Cd 0.2 S / PDI composite photocatalyst is used to degrade polybrominated diphenyl ethers in wastewater.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention adopts the common chemical synthesis method to synthesize Zn 0.8 Cd 0.2 Compared with conventional PDI, S / PDI composite photocatalyst saves the time required for self-assembly and eliminates harsh solvent and atmosphere conditions;

[0023] (2) Compared with traditional PDI free radical catalysts, the catalyst synthesized in this scheme can be stored at room temperature and pressure under air conditions, and the activation process does not require strong reducing agents such as hydrazine hydrate or triethylamine that are not environmentally friendly. It can be converted into a free radical form only by light exposure.

[0024] (3) The present invention combines PDI with Zn 0.8 Cd 0.2 S is compounded. Since the PDI molecule contains a perylene core structure, it has a strong electron-withdrawing property. Under light excitation, Zn 0.8 Cd 0.2 The conduction band of S nanoparticles can conduct two electrons to each PDI molecule, and PDI is activated to become: 2- , the catalyst in the free radical state increases the separation of electron-hole pairs, thereby improving the photocatalytic performance of the composite material;

[0025] (4) After light exposure, Zn 0.8 Cd 0.2 S / PDI to Zn 0.8 Cd 0.2 S / :PDI 2- , transforming from reverse KIE to positive KIE, and achieving efficient dehalogenation of aromatic halides through a diradical attack pathway. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 PDI, Zn 0.8 Cd 0.2 S and different proportions of Zn 0.8 Cd 0.2 XRD pattern of S / PDI composite photocatalyst.

[0027] Figure 2 A is Zn 0.8 Cd 0.2 SEM image of S, B is the SEM image of PDI, C and D are 10% Zn 0.8 Cd 0.2 SEM image of S / PDI composite photocatalyst, E is 10% Zn 0.8 Cd 0.2 Mapping diagram of S / PDI composite photocatalyst.

[0028] Figure 3 PDI, Zn 0.8 Cd 0.2 S, 10% Zn before illumination 0.8 Cd 0.2 S / PDI composite photocatalyst and 10% Zn after illumination 0.8 Cd 0.2 PL image of S / PDI composite photocatalyst.

[0029] Figure 4 PDI, Zn 0.8 Cd 0.2 S and 10% Zn 0.8 Cd 0.2 UV-visible absorption graph of S / PDI composite photocatalyst.

[0030] Figure 5 A is PDI and 10% Zn 0.8 Cd 0.2 C1s spectrum of S / PDI composite photocatalyst, B is PDI and 10% Zn 0.8 Cd 0.2 N1s spectrum of S / PDI composite photocatalyst, C is PDI and 10% Zn 0.8 Cd 0.2 O1s spectrum of S / PDI composite photocatalyst, D is Zn 0.8 Cd 0.2 S and 10% Zn 0.8 Cd 0.2 S2p spectrum of S / PDI composite photocatalyst, E is Zn 0.8 Cd 0.2 S and 10% Zn 0.8 Cd 0.2 Cd3d spectrum of S / PDI composite photocatalyst, F is Zn 0.8 Cd 0.2 S and 10% Zn 0.8 Cd 0.2 Zn2p spectrum of S / PDI composite photocatalyst.

[0031] Figure 6 10% Zn 0.8 Cd 0.2 S / PDI composite photocatalyst under AM 1.5 and Xe lamp (1000mW·cm -2 )Degradation performance of decabromodiphenyl ether under light.

[0032] Figure 7 Zn 0.8 Cd 0.2 Flow chart of light activation of S / PDI composite photocatalyst. DETAILED DESCRIPTION

[0033] The technical scheme of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. The experimental methods used in the following embodiments are conventional methods unless otherwise specified.

[0034] The 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), imidazole, β-alanine, cetyltrimethylammonium bromide (CTAB), hexamethylenetetramine, citric acid monohydrate, cadmium nitrate tetrahydrate, zinc nitrate hexahydrate and thioacetamide used in the present invention were all analytically pure and purchased from Aladdin (Shanghai) Biochemical Technology Co., Ltd.

[0035] The photocatalytic activity of the photocatalyst prepared in the present invention was evaluated in a DW-01 photochemical reactor (purchased from Yangzhou University City Technology Co., Ltd.) under irradiation with visible light lamp and focused natural sunlight. - 5 mol / L (the solution composition is tetrahydrofuran: ethanol: deionized water = 1:9:99 by volume) decabromodiphenyl ether simulated wastewater was added into the reactor and its initial value (A0) was determined. Then the prepared photocatalyst was added, magnetic stirring was performed and nitrogen was introduced into the aeration device to keep the solution in an anaerobic state. During the illumination process, samples were taken for analysis at intervals of 5s to 1h. After centrifugation, the supernatant was taken and the substrate concentration (A0) was determined by high performance liquid chromatography. i ), the bromide ion concentration (c i ), and through the formula: Dr = [1-A i / A0] × 100% to calculate the degradation rate, and the formula Y = (c i / 10 -4 )×100% to calculate the degradation efficiency. A0 is the concentration of decabromodiphenyl ether solution when adsorption equilibrium is reached, A i is the concentration of decabromodiphenyl ether solution measured by regular sampling, c i The bromide ion concentration of decabromodiphenyl ether solution was measured by regular sampling.

[0036] Embodiment 1:

[0037] (1) Preparation of PDI: 1.376 g of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), 18 g of imidazole and 2.5 g of β-alanine were weighed and mixed, and calcined at 120°C in a tube furnace for 5 h under nitrogen protection. The resulting red solid was dispersed in 100 mL of ethanol, and 600 mL of 2 M HCl solution was added and stirred overnight. The mixture was washed with deionized water by centrifugation until neutral, and finally dried in a vacuum drying oven at 60°C overnight to obtain PDI.

[0038] (2) Zn 0.8 Cd 0.2Preparation of S / PDI composite photocatalyst: Weigh 0.86g CTAB and add it to 100mL deionized water, heat to 30℃ and stir until dissolved, then add 0.327g hexamethylenetetramine, 0.243g citric acid monohydrate, 0.283g cadmium nitrate tetrahydrate, 1.093g zinc nitrate hexahydrate and 0.025g PDI in turn, stir for 15 minutes, heat to 85℃ and add 0.345g thioacetamide, condense and reflux for 5h. Cool to room temperature, centrifuge the obtained product, wash repeatedly with 0.3% NaCl solution and deionized water, and finally dry in vacuum at 60℃ to obtain the final product, photosensitive activated 1% Zn 0.8 Cd 0.2 S / PDI composite photocatalyst;

[0039] (3) The sample in (2) was subjected to a photocatalytic degradation test in a photochemical reactor under a visible light lamp. The degradation efficiency of decabromodiphenyl ether by the photocatalyst was measured to be 16.9% within 1 hour, which was not enough to completely degrade decabromodiphenyl ether.

[0040] Embodiment 2:

[0041] (1) Preparation of PDI: 1.376 g of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), 18 g of imidazole and 2.5 g of β-alanine were weighed and mixed, and calcined at 120°C in a tube furnace for 5 h under nitrogen protection. The resulting red solid was dispersed in 100 mL of ethanol, and 600 mL of 2 M HCl solution was added and stirred overnight. The mixture was washed with deionized water by centrifugation until neutral, and finally dried in a vacuum drying oven at 60°C overnight to obtain PDI.

[0042] (2) Zn 0.8 Cd 0.2 Preparation of S / PDI composite photocatalyst: Weigh 0.86g CTAB and add it to 100mL deionized water, heat to 30℃ and stir until dissolved, then add 0.327g hexamethylenetetramine, 0.243g citric acid monohydrate, 0.283g cadmium nitrate tetrahydrate, 1.093g zinc nitrate hexahydrate and 0.125g PDI in turn, stir for 15 minutes, heat to 85℃ and add 0.345g thioacetamide, condense and reflux for 5h. Cool to room temperature, centrifuge the obtained product, wash repeatedly with 0.3% NaCl solution and deionized water, and finally dry in vacuum at 60℃ to obtain the final product, photosensitive activated 5% Zn 0.8 Cd 0.2 S / PDI composite photocatalyst;

[0043] (3) The sample in (2) was subjected to a photocatalytic degradation test in a photochemical reactor under a visible light lamp. It was found that the degradation efficiency of decabromodiphenyl ether by the photocatalyst reached 25.0% within 1 hour, which was not enough to completely degrade decabromodiphenyl ether.

[0044] Embodiment 3:

[0045] (1) Preparation of PDI: 1.376 g of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), 18 g of imidazole and 2.5 g of β-alanine were weighed and mixed, and calcined at 120°C in a tube furnace for 5 h under nitrogen protection. The resulting red solid was dispersed in 100 mL of ethanol, and 600 mL of 2 M HCl solution was added and stirred overnight. The mixture was washed with deionized water by centrifugation until neutral, and finally dried in a vacuum drying oven at 60°C overnight to obtain PDI.

[0046] (2) Zn 0.8 Cd 0.2 Preparation of S / PDI composite photocatalyst: Weigh 0.86g CTAB and add it to 100mL deionized water, heat to 30℃ and stir until dissolved, then add 0.327g hexamethylenetetramine, 0.243g citric acid monohydrate, 0.283g cadmium nitrate tetrahydrate, 1.093g zinc nitrate hexahydrate and 0.25g PDI in turn, stir for 15 minutes, heat to 85℃ and add 0.345g thioacetamide, condense and reflux for 5h. Cool to room temperature, centrifuge the obtained product, wash repeatedly with 0.3% NaCl solution and deionized water, and finally dry in vacuum at 60℃ to obtain the final product, photosensitive activated 10% Zn 0.8 Cd 0.2 S / PDI composite photocatalyst;

[0047] (3) The sample in (2) was subjected to a photocatalytic degradation test in a photochemical reactor under a visible light lamp. It was found that the degradation efficiency of decabromodiphenyl ether by the photocatalyst reached 46.3% within 1 hour and 98% within 6 hours, thus achieving complete degradation of decabromodiphenyl ether.

[0048] Embodiment 4:

[0049] (1) Preparation of PDI: 1.376 g of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), 18 g of imidazole and 2.5 g of β-alanine were weighed and mixed, and calcined at 120°C in a tube furnace for 5 h under nitrogen protection. The resulting red solid was dispersed in 100 mL of ethanol, and 600 mL of 2 M HCl solution was added and stirred overnight. The mixture was washed with deionized water by centrifugation until neutral, and finally dried in a vacuum drying oven at 60°C overnight to obtain PDI.

[0050] (2) Zn 0.8 Cd0.2 Preparation of S / PDI composite photocatalyst: Weigh 0.86g CTAB and add it to 100mL deionized water, heat to 30℃ and stir until dissolved, add 0.327g hexamethylenetetramine, 0.243g citric acid monohydrate, 0.283g cadmium nitrate tetrahydrate, 1.093g zinc nitrate hexahydrate and 0.375g PDI in turn, stir for 15 minutes, heat to 85℃ and add 0.345g thioacetamide, condense and reflux for 5h. Cool to room temperature, centrifuge the obtained product, wash repeatedly with 0.3% NaCl solution and deionized water, and finally dry in vacuum at 60℃ to obtain the final product, photosensitive activated 15% Zn 0.8 Cd 0.2 S / PDI composite photocatalyst;

[0051] (3) The sample in (2) was subjected to a photocatalytic degradation test in a photochemical reactor under a visible light lamp. It was found that the degradation efficiency of decabromodiphenyl ether by the photocatalyst reached 25.0% within 1 hour, which was not enough to completely degrade decabromodiphenyl ether.

[0052] Figure 1 PDI, Zn 0.8 Cd 0.2 S and different proportions of Zn 0.8 Cd 0.2 XRD pattern of S / PDI composite photocatalyst; the figure clearly shows the 0.8 Cd 0.2 The characteristic peaks of S, Zn 0.8 Cd 0.2 S / PDI composite photocatalysts have been detected to contain PDI and Zn 0.8 Cd 0.2 The characteristic peak of S, and the intensity of the PDI characteristic peak varies with the ratio. In addition, we found that the photosensitive Zn 0.8 Cd 0.2 The S / PDI composite photocatalyst did not change the PDI and Zn 0.8 Cd 0.2 The crystal structure of S.

[0053] Figure 2 A is Zn 0.8 Cd 0.2 SEM image of S, B is the SEM image of PDI, C and D are 10% Zn 0.8 Cd 0.2 SEM image of S / PDI composite photocatalyst, E is 10% Zn 0.8 Cd 0.2 Mapping diagram of S / PDI composite photocatalyst; From Figures C, D and E, we can see that the spherical Zn 0.8 Cd0.2 The S particles (Figure A) are evenly dispersed on the PDI with long flakes (Figure B), indicating that 10% Zn 0.8 Cd 0.2 The S / PDI composite photocatalyst has been successfully synthesized.

[0054] Figure 3 PDI, Zn 0.8 Cd 0.2 S, 10% Zn before illumination 0.8 Cd 0.2 S / PDI composite photocatalyst and 10% Zn after illumination 0.8 Cd 0.2 PL image of S / PDI composite photocatalyst; the image shows that the strong emission peaks of PDI are concentrated at 550, 590 and 705nm. 0.8 Cd 0.2 After S, 10% Zn 0.8 Cd 0.2 The strong emission peak of S / PDI composite photocatalyst is only 705nm, indicating that 10% Zn 0.8 Cd 0.2 The photogenerated electron-hole pairs in S / PDI composites can be efficiently transferred at the heterojunction interface and have better performance than PDI and Zn 0.8 Cd 0.2 S has higher photocatalytic activity; at the same time, the fluorescence intensity decreases and slightly blue-shifts after illumination, indicating that 10% Zn 0.8 Cd 0.2 The structure of the S / PDI composite material has changed compared to the monomer and it has been verified that the material has better performance under simulated sunlight.

[0055] Figure 4 PDI, Zn 0.8 Cd 0.2 S and 10% Zn 0.8 Cd 0.2 UV-visible absorption diagram of S / PDI composite photocatalyst, indicating that Zn 0.8 Cd 0.2 S doping in PDI can greatly expand the visible light absorption region and enhance the photocatalytic efficiency.

[0056] Figure 5 PDI, Zn 0.8 Cd 0.2 S and 10% Zn 0.8 Cd 0.2 XPS spectra of S / PDI composite photocatalysts, showing that 10% Zn 0.8 Cd 0.2 S / PDI composite photocatalyst and PDI, Zn 0.8 Cd0.2 The difference in crystal structure.

[0057] Figure 6 10% Zn 0.8 Cd 0.2 The S / PDI composite photocatalyst was exposed to AM1.5 and xenon lamp (1000 mW·cm -2 ) was used to study the degradation performance of decabromodiphenyl ether. It was found that the performance under simulated sunlight was higher than that under xenon lamp irradiation, which verified that the material had enhanced ultraviolet absorption and was more conducive to the practical application of the catalyst.

[0058] Figure 7 Zn 0.8 Cd 0.2 Flow chart of light activation of S / PDI composite photocatalyst.

[0059] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A photosensitive activated Zn 0.8 Cd 0.2 The method for preparing the S / PDI composite photocatalyst is characterized in that: The following steps are involved: (1) Preparation of PDI: 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), imidazole and β-alanine were mixed, calcined in a tube furnace under nitrogen protection for a period of time, the resulting red solid was dispersed in ethanol, HCl solution was added and stirred overnight, washed with deionized water by centrifugation, and finally dried in a vacuum drying oven overnight to obtain the desired PDI; (2) Photosensitive activated Zn 0.8 Cd 0.2 Preparation of S / PDI composite photocatalyst: CTAB is added to deionized water and stirred until dissolved. Hexamethylenetetramine, citric acid monohydrate, cadmium nitrate tetrahydrate, zinc nitrate hexahydrate and PDI prepared in step (1) are added in sequence and heated. Finally, thioacetamide is added. After condensation and reflux, stirring and reacting for a period of time, the mixture is cooled to room temperature. The obtained product is centrifuged, washed repeatedly with NaCl solution and deionized water, and finally dried in vacuum to obtain the final product, photosensitive activated Zn 0.8 Cd 0.2 S / PDI composite photocatalyst.

2. The preparation method according to claim 1, characterized in that In step (1), the molar ratio of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), imidazole and β-alanine is 1:50:5; and the concentration of the HCl solution is 2 mol / L.

3. The preparation method according to claim 1, characterized in that: In step (1), the calcination temperature is 100-120° C. and the calcination time is 4-5 hours.

4. The preparation method according to claim 1, characterized in that: In step (1), the vacuum drying temperature is 60 to 70° C. and the time is 10 to 12 hours.

5. The preparation method according to claim 1, characterized in that: In step (2), the usage ratio of CTAB, hexamethylenetetramine, citric acid monohydrate, cadmium nitrate tetrahydrate, zinc nitrate hexahydrate, PDI and thioacetamide is 0.86g::0.327g:0.243g:0.283g:1.093g:0.025~3.75g:0.345g.

6. The preparation method according to claim 1, characterized in that: In step (2), the heating temperature is 80-85° C. and the heating time is 5-6 hours.

7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the NaCl solution is 0.3%.

8. The preparation method according to claim 1, characterized in that: In step (2), the vacuum drying temperature is 60-70° C. and the time is 10-12 hours.

9. A photosensitive activated Zn 0.8 Cd 0.2 The S / PDI composite photocatalyst is characterized by: It is prepared by the preparation method according to any one of claims 1 to 8, wherein PDI accounts for Zn 0.8 Cd 0.2 The molar percentage of S is 1% to 15%.

10. The photosensitive activated Zn 0.8 Cd 0.2 The S / PDI composite photocatalyst is used to degrade polybrominated diphenyl ethers in wastewater.

Citation Information

Patent Citations

  • Preparation method of composite material of Zn0.8Cd0.2S and graphene

    CN103316694A

  • Supermolecule heterojunction organic photocatalyst and preparation method and application method thereof

    CN110841711A

  • Preparation method of In2O3 / Zn0.8Cd0.2S photocatalytic nanoreactor

    CN112973732A